Take-home naloxone in multicentre emergency settings: the TIME feasibility cluster RCT - Helen Snooks; Jonathan Benger; Fiona Bell; Sarah Black; Simon Dixon; Helena Emery; Bridie Angela Evans; Gordon Fuller; Rebecca Hoskins; Jane Hughes; Jenna Jones; Matthew Jones; et al. (Health Technology Assessment, 2024)
Background Opioids kill more people than any other drug. Naloxone is an opioid antagonist which can be distributed in take-home ‘kits’ for peer administration (take-home naloxone). Aim To determine the feasibility of carrying out a definitive randomised controlled trial of take-home naloxone in emergency settings. Design We used Welsh routine data (2015–21) to test the feasibility of developing a discriminant function to identify people at high risk of fatal opioid overdose. We carried out a cluster randomised controlled trial and qualitative study to examine experiences of service users and providers. We assessed feasibility of intervention and trial methods against predetermined progression criteria related to: site sign-up, staff trained, identification of eligible patients, proportion given kits, identification of people who died of opioid poisoning, data linkage and retrieval of outcomes. Setting This study was carried out in the emergency environment; sites comprised an emergency department and associated ambulance service catchment area. Participants At intervention sites, we invited emergency department clinicians and paramedics to participate. We recruited adult patients who arrived at the emergency department or were attended to by ambulance paramedics for a problem related to opioid use with capacity to consent to receiving the take-home naloxone and related training. Interventions Usual care comprised basic life support plus naloxone by paramedics or emergency department staff. The take-home naloxone intervention was offered in addition to usual care, with guidance for recipients on basic life support, the importance of calling the emergency services, duration of effect, safety and legality of naloxone administration. Results Discriminant function With low numbers of opioid-related deaths (1105/3,227,396) and a high proportion having no contact with health services in the year before death, the predictive link between death and opioid-related healthcare events was weak. Logistic regression models indicated we would need to monitor one-third of the population to capture 75% of the decedents from opioid overdose in 1-year follow-up. Randomised controlled trial Four sites participated in the trial and 299 of 687 (44%) eligible clinical staff were trained. Sixty take-home naloxone kits were supplied to patients during 1-year recruitment. Eligible patients were not offered take-home naloxone kits 164 times: ‘forgot’ (n = 136); ‘too busy’ (n = 15); suspected intentional overdose (n = 3). Qualitative interviews Service users had high levels of knowledge about take-home naloxone. They were supportive of the intervention but noted concerns about opioid withdrawal and resistance to attending hospital for an overdose. Service providers were positive about the intervention but reported barriers including difficulty with consenting and training high-risk opioid users. Health economics We were able to calculate costs to train staff at three sites (£40 per AS and £17 in Site 1 ED). No adverse events were reported. Progression criteria were not met – fewer than 50% of eligible staff were trained, fewer than 50% of eligible patients received the intervention and outcomes were not retrieved within reasonable timescales. Future work The take-home naloxone intervention needs to be developed and evaluated in emergency care settings, with appropriate methods. Limitations The Take-home naloxone Intervention Multicentre Emergency setting study was interrupted by coronavirus disease. Conclusions This study did not meet progression criteria for intervention or trial methods feasibility, so outcomes were not followed up and a fully powered trial is not planned. Trial registration This trial is registered as ISRCTN13232859. Funding This award was funded by the National Institute for Health and Care Research (NIHR) Health Technology Assessment programme (NIHR award ref: 16/91/04) and is published in full in Health Technology Assessment; Vol. 28, No. 74. See the NIHR Funding and Awards website for further award information. Plain language summary Emergency ambulance staff and doctors in the emergency department regularly administer naloxone to people who have overdosed, reversing effects of the opioid – so-called ‘take-home naloxone’ – to administer to others in an emergency. We don’t know whether take-home naloxone saves lives. We carried out this feasibility study to see whether: we could identify a high-risk population to include in a trial to determine whether take-home naloxone reduces deaths from overdose ambulance paramedics and emergency department staff could be trained, and would then give out take-home naloxone kits to drug users they see. We included four areas in the study. We randomly selected two for distribution of take-home naloxone to patients at risk of or following an overdose by emergency department clinicians and local ambulance paramedics. We attempted to identify people at high risk of death from opioid overdose. We collected data about patients that were eligible and received take-home naloxone in the two intervention areas. We carried out interviews to find out about the views of patients and staff who gave out the kits. At the start, we agreed criteria that should be met for us to recommend that a full evaluation be carried out. We could not reliably identify people at high risk of death from opioid overdose, as deaths were rare in the population, and previous health service usage was variable. Less than half of eligible staff were trained to supply take-home naloxone (299/687, 44%), and less than half of eligible patients were given take-home naloxone (60/277, 21.7%) over 1 year. Patients were not offered take-home naloxone because staff forgot, were too busy or suspected an intentional overdose. Other patients left before receiving a kit. Service users liked the idea of take-home naloxone kits being provided in the emergency setting but reported resistance to attending hospital following an overdose. Service providers were supportive of providing take-home naloxone in the emergency setting but reported challenges in consent and training. Conclusion This study found that it was not feasible to deliver or evaluate this form of take-home naloxone, using this study design, in emergency care. Scientific summary Parts of this summary have been reproduced from Jones M, Bell F, Benger J, Black S, Buykx P, Dixon S, et al. Protocol for Take-home naloxone In Multicentre Emergency (TIME) settings: feasibility study. Pilot Feasib Stud 2020;6(1):1–10. This is an Open Access article distributed in accordance with the terms of the Creative Commons Attribution (CC BY 4.0) licence, which permits others to distribute, remix, adapt and build upon this work, for commercial use, provided the original work is properly cited. See: https://creativecommons.org/licenses/by/4.0/. The text below includes minor additions and formatting changes to the original text. Background Opioids, such as heroin, kill more people worldwide by overdose than any other type of drug, and death rates associated with opioid poisoning in the United Kingdom (UK) are at record levels. Naloxone is an opioid antagonist which can be distributed in ‘kits’ for administration by witnesses in an overdose emergency. This intervention is known as take-home naloxone (THN). We know that THN can save lives on an individual level, but there is currently limited evidence about the effectiveness of THN distribution on an aggregate level, in specialist drug service settings or in emergency service (ES) settings. Notably, we do not know whether THN kits reduce deaths from opioid overdose in at-risk populations, if there are unforeseen harms associated with THN distribution or if THN is cost-effective. To address this research gap, we aimed to determine the feasibility of a fully powered cluster randomised controlled trial (RCT) of THN distribution in emergency settings. Aim To determine the feasibility of carrying out a definitive RCT of THN in emergency settings. Objectives To determine: the best form of THN kit, training and delivery whether a trial clustered by emergency department (ED) catchment area and the associated ambulance service (AS) is deliverable, as assessed against predefined progression criteria related to intervention, trial design and methods. Design We assessed feasibility of intervention and trial methods based upon the following predetermined progression criteria. Intervention feasibility Sign-up of four sites, including ≥ 50% eligible staff to complete training in delivering the intervention at each intervention site. Identification of ≥ 75% of people who have presented to ED or AS with opioid overdose or an opioid use-related problem over a 12-month period. THN kits issued to ≥ 50% eligible patients over a 12-month period at intervention sites. Serious adverse event rate [to be defined in agreement with Data Monitoring and Ethics Committee (DMEC)] of no more than 10% difference in intervention sites to control sites at the conclusion of recruitment. Trial methods feasibility Identification and inclusion for follow-up of ≥ 75% of people who died of opioid poisoning in the following year in the study areas according to Office of National Statistics (ONS) mortality data (previous ONS data suggest between 140 and 180 such deaths across the 4 participating sites during the study period). Matching and data linkage in ≥ 90% of cases not dissented at the conclusion of quantitative data collection. Retrieval of primary and secondary outcomes from National Health Service (NHS) Digital and National Welsh Informatics Service within 6 months of projected timeline. As the intervention tested is for administration to recipients of the THN kits and peers who may suffer an overdose, we needed to find a way to identify cohorts to include in outcome comparisons. We therefore analysed Welsh routine data to test the feasibility of developing a discriminant function to identify a high-risk population for fatal opioid overdose. We scoped anonymised routine retrospective data from 1 January 2015 to 30 November 2021, sourced from the Welsh Demographic Service Dataset (WDSD) to define the study population. To categorise death associated with an opioid overdose, the annual district death extract (ADDE) dataset was used in conjunction with the WDSD to calculate an individual-level study end date. Finally, we considered critical care, ED and hospital admissions as well as substance misuse treatment for the 36 months up to the end of the study period. We carried out a RCT clustered by site in the emergency environment with a qualitative study to examine processes of implementation, patient safety, costs of training NHS staff and experiences of service users and providers. Two intervention sites (paired ED and local AS catchment area) were randomly selected from the four participating sites. Usual practice was continued in the other two sites, acting as controls. Alongside the RCT, we collected qualitative data via semistructured interviews with service users from substance use treatment centres and third-sector organisations. The interview questions were guided by literature around opioid overdose experience and emergency naloxone use, with the aim to explore how opioid users interact with the knowledge, behaviour and attitudes towards the use of THN kits and training to use the kits. Focus groups and interviews with service providers (paramedics and ED clinical staff) were conducted to discuss barriers in the provision of THN in the emergency setting as well as facilitators to this implementation. We assessed the feasibility of collecting costs associated with THN provision in the emergency setting by measuring the health service contacts and incorporating healthcare resource groups (HRGs) into the analysis to produce an overall cost. Setting This feasibility study was carried out in the emergency care environment, across study sites each centred on a receiving ED and defined geographically as the local AS catchment area for that receiving ED. Participants At intervention sites, we invited ED clinicians and paramedics to participate in the trial and recruited adult patients who arrived at the ED or were attended by ambulance paramedics for a problem related to opioid use with capacity to consent to receiving the THN and related training. Participants were to be identified for outcome comparison by application of the discriminant function, if completed, to the study site general populations. Interventions Usual care comprised administration of basic life support plus naloxone by paramedics or ED staff. The THN intervention was offered in addition to usual care and included a multi dose THN kit (Prenoxad) containing 2 mg naloxone hydrochloride 1 mg/1 ml solution for intramuscular (IM) injection, and instructions on the correct administration of the naloxone dose. Recipients also received guidance on: BLS; the importance of calling the ES; duration of effect; the safety of naloxone in terms of adverse events and overdose; and the legality of bystander administration of naloxone. Results TABLE S1Assessment against preset progression criteria Criteria Achieved Criteria met Sign-up of four sites, including ≥ 50% eligible staff to complete training in delivering the intervention at each intervention site Site 1: ED trained 81.1%, AS trained 54% of eligible staffSite 2: ED trained 8.1%, AS trained 33.8% of eligible staff No Identification of ≥ 75% of people who have presented to ED or AS with opioid overdose or an opioid use-related problem over a 12-month period Unable to assess Not known THN kits issued to ≥ 50% eligible patients over a 12-month period at intervention sites 21.7% of eligible patients were given kits No Serious adverse event rate (to be defined in agreement with the DMEC) of no more than 10% difference in intervention sites to control sites at the conclusion of recruitment No serious adverse events were reported Yes Identification and inclusion for follow-up of ≥ 75% of people who died of opioid poisoning in the following year in the study areas according to ONS mortality data (previous ONS data suggest between 140 and 180 such deaths across the four participating sites during the study period) We were able to identify decedents from opioid poisoning in Wales but were unable to produce a discriminant function which included this group in a sufficiently small section of the general population, or to test these methods in a second population No Matching and data linkage in ≥ 90% of cases not dissented at the conclusion of quantitative data collection Due to significant delays in permissions processes for routine- linked data retrieval from NHS Digital, and low administration of THN kits, we did not attempt to match and link records for patients recruited to the trial No Retrieval of routinely recorded primary and secondary outcomes from national repositories within six-months of projected timeline Again, due to significant delays in permissions processes for routine- linked data retrieval, and low administration of THN kits, we did not attempt to retrieve routinely recorded primary and secondary outcomes No Discriminant function With low numbers of opioid-related deaths (1105/3,227,396) and a high proportion of them having no contact with health services in the year before death, the predictive link between death and opioid-related healthcare events was weak. Logistic regression models indicated we would need to monitor one-third of the population to capture 75% of the decedents from opioid overdose in 1-year follow-up. RCT In total, 299 of 687 (43.5%) eligible staff were trained to supply THN kits to eligible patients at the two sites (Site 1: ED n = 107, AS n = 121; Site 2: ED n = 25, AS n = 46). Sixty THN kits were supplied to eligible patients during the recruitment period (Site 1: ED n = 36, AS n = 4; Site 2: ED n = 16, AS n = 4). Eligible patients were recorded as not being offered THN kits 164 times, with reasons reported for not offering eligible patients kits: staff forgot (n = 136); staff too busy (n = 15); and suspected intentional overdose (n = 3). Staff recorded 626 people as being considered for inclusion but found not to be eligible, with reasons listed as: uncooperative including being abusive towards staff (n = 55); lack of capacity (n = 35); reduced consciousness level (n = 41); patient in custody (n = 21); and patient absconded (n = 161). Qualitative interviews Service users had high levels of knowledge about THN, with variable previous access to kits. They generally supported the provision of THN kits and training in the emergency setting and felt that it should be expanded further to chemists and needle exchanges. They also noted the importance of including loved ones in training and felt that this gave them a sense of empowerment and motivation to help others in an overdose situation. They noted concerns with regards to opioid withdrawal and resistance to attending hospital for an overdose. The service users reported that the provision of THN kits and training to friends and family of opioid users would possibly be more beneficial and believed that incorporating THN provision into normal practice would help mitigate some of these barriers. Interviews and focus groups with service providers found that they were supportive about the provision of THN kits and training in the emergency setting. However, they also reported barriers including difficulties consenting and training opioid users, a high turnover of staff impacting the cascade of the intervention as well as negative attitudes towards the patient group and the coronavirus disease 2019 (COVID-19) pandemic. No adverse events were reported. Conclusion This study did not meet progression criteria for intervention or trial methods feasibility, so outcomes were not followed up and a fully powered trial is not planned. There does appear to be appetite for THN kit provision and training in the emergency setting. We conclude that the THN intervention as defined and administered in the Take-home naloxone Intervention Multicentre Emergency setting (TIME) study was not feasible and should not therefore go forward to full trial. However, there may be space for further development of this complex intervention in emergency care – for example, for protocols to allow administration to family and friends of opioid users; as well as methods for definition and identification of study cohorts for outcome comparisons. Trial registration This trial is registered as ISRCTN13232859. Funding This award was funded by the National Institute for Health and Care Research (NIHR) Health Technology Assessment programme (NIHR award ref: 16/91/04) and is published in full in Health Technology Assessment; Vol. 28, No. 74. See the NIHR Funding and Awards website for further award information.